Rational design of D–π–D hole-transporting materials for efficient perovskite solar cells. (27th September 2021) - Ou, Yang Mei; Xie, Lin; Wu, Tai; Zhao, Rong Jun; Wang, Peng; Zhao, Yuan Ju; Liu, Gao Yuan; Lai, Qian; Zhu, Li Qiong; Hua, Yong
Abstract : D–π–D hole-transporting materials are designed via facile approaches for efficient perovskite solar cells. Suitable band alignment and high hole mobility by strengthening the conjugation in the core allow effective hole extraction. Abstract : Organic–inorganic halide perovskites (OIHPs) are nature-abundant raw materials with prospects as a low-cost renewable energy source encouraged by the solution-processed capability of OIHPs. However, the application of an expensive hole-transporting material (HTM), such as 2, 2′, 7, 7′-tetrakis ( N, N -di- p -methoxyphenyl-amine)-9, 9′-spirobifluoren (Spiro-OMeTAD), in the most efficient OIHP solar cells limits their commercialization at a large scale. Here, a series of D–π–D hole-transporting materials are designed and synthesized from inexpensive starting materials with high yield via simple synthetic routes for application in OIHP solar cells. It is found that strengthening the conjugation by inserting a conjugated bridge of (3, 7-di(thiophen-2-yl)dibenzo[ b, d ]thiophene) (QY3) in the synthetic molecule, leads to a higher hole mobility and deeper HOMO level, resulting in an increased fill factor, improved open-circuit voltage and increased power conversion efficiency of 19.28%, which is comparable to that of OIHP solar cells based on Spiro-OMeTAD (19.30%). The results show that QY3-HTM could be a promising candidate for low-cost OIHP solar cells. The present work provides a guideline for rational design via prudent control of the core units of the hole transport materials for application in low-cost OIHP solar cells.